Amino Acid Profile of Luminal A and B Subtypes Breast Cancer - Sonar Soni Panigoro; Arif Kurniawan; Ramadhan Ramadhan; Ninik Sukartini; Herqutanto Herqutanto; Rafika Indah Paramita; Ferry Sandra (The Indonesian Biomedical Journal, 2023)
BACKGROUND: Amino acids are important for proliferation and maintenance of tumor cells. Breast cancer patients were found to have significant changes in the number of amino acids, which are assumed to be correlated with the molecular subtypes of breast cancer. Therefore, current study was conducted to analyze plasma amino acids in breast cancer patients with luminal A and B subtypes.METHODS: Breast cancer and control subjects were recruited, and venous blood was collected for the measurement of plasma amino acids. Total 19 plasma amino acids were measured using reverse-phase high-performance liquid chromatography with C18 column. Mean comparison for normally distributed and homogeneous data was further analzyed using independent sample T-test, with p<0.05 was considered as significant.RESULTS: From total 19 amino acids, only 7 amino acids; cysteine, glutamic acid, histidine, ornithine, threonine, tyrosine, valine, were statistically different between the healthy control and breast cancer subjects. Eventhough no amino acids was found to be statistically different between breast cancer subjects with luminal A and B subtypes, but some amino acids were found to be significantly different when correlated to various breast cancer risk factors.CONCLUSION: Amino acid profile of patients with Luminal A and B subtypes of breast cancer differs compared to healthy controls and is also correlated with breast cancer risk factors. Increase in cysteine level in Luminal A subtype patients and decrease of alanine and leucine in Luminal B subtype patients can be used as a biomarker.KEYWORDS: amino acid, plasma, breast cancer, risk factor, biomarker